2005
DOI: 10.1128/jcm.43.4.1722-1726.2005
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Hepatitis C Virus Core Antigen Assay for Screening of a Population Undergoing Routine Medical Checkup

Abstract: We studied the usefulness of the recently designed Trak-C assay for the detection and quantification of the hepatitis C virus (HCV) core antigen (Ag) for the screening of HCV infection in 4,201 subjects selected from 74,150 consecutive volunteers undergoing routine medical checkups. Subjects were selected for screening because they had risk factors (group II, n ‫؍‬ 321) and/or elevated alanine transaminase activity (group I, n ‫؍‬ 3847). Initially, the anti-HCV antibody assay and the Trak-C assay were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
2
21
1
Order By: Relevance
“…Many studies have observed a very good correlation (0.72 Ͻ r Ͻ 0.80) between quantification methods of HCV RNA and HCV CA in HCV-monoinfected patients (7,12,20,22,24). In HCV/HIV-coinfected patients, we also found an excellent correlation at baseline between these two markers of HCV infection (0.92).…”
Section: Discussionsupporting
confidence: 63%
“…Many studies have observed a very good correlation (0.72 Ͻ r Ͻ 0.80) between quantification methods of HCV RNA and HCV CA in HCV-monoinfected patients (7,12,20,22,24). In HCV/HIV-coinfected patients, we also found an excellent correlation at baseline between these two markers of HCV infection (0.92).…”
Section: Discussionsupporting
confidence: 63%
“…The importance of HCVcoreAg in the early diagnosis of HCV infection has been established in many studies (25)(26)(27). Also, the monitoring of HCVcoreAg during the treatment course can help to predict responses to anti-viral therapy (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of antibodies has some limitations, such as lack of antibodies during the early stage of infection and in immunodeficient patients, thereby leading to false-negative results (2). It is difficult to generate high-quality antibodies against core protein, although detection of HCV core antigen present in serum is highly sensitive and specific (3).…”
mentioning
confidence: 99%